Vitamin B12 Deficiency in Persons with Intellectual Disability in a Vegetarian Residential Care Community - Mohammed Morad; Mark Gringols; Isack Kandel; Joav Merrick (The Scientific World Journal)
The goal of this study was to determine the prevalence of vitamin B12 deficiency among intellectually disabled persons in a vegetarian remedial community in Israel. In this community, 47 individuals with intellectual disability (ID) live in 7 enlarged families in a kibbutz style agricultural setting. These 47 individuals and 17 of their caregivers were screened for vitamin B12 deficiency. There were 25.5% of the disabled vs. 11.8% of the caregivers found to have levels of vitamin B12 lower than 157 pg/ml. It is concluded that persons with ID in this vegetarian residential care community seemed to be at a higher risk for vitamin B12 deficiency.